Facilitating primary care provider use in a patient-centered medical home intervention study for chronic hemodialysis patients. Issue 3 (23rd May 2018) - Chukwudozie, Ifeanyi Beverly; Fitzgibbon, Marian L; Schiffer, Linda; Berbaum, Michael; Gilmartin, Cheryl; David, Pyone; Ekpo, Eson; Fischer, Michael J; Porter, Anna C; Aziz-Bradley, Alana; Hynes, Denise M
Abstract: Patients with chronic kidney disease have a high disease burand may benefit from primary care services and care coord A medical home model with direct access to primary care services is one approach that may address this need, yet has not been examined. As a substudy of the Patient-Centered Outcomes Research Institute (PCORI) patient-centered medical home for kidney disease (PCMH-KD) health system intervention study, we examined the uptake of free primary care physician (PCP) services. The PCORI PCMH-KD study was an initial step toward integrating PCPs, a nurse coordinator, a pharmacist, and community health workers (CHWs) within the health care delivery team. Adult chronic hemodialysis (CHD) at two urban dialysis centers were enrolled in the intervention. We examined trends and factors associated with the use of the PCMH-KD PCP among two groups of patients based on their report of having a regular physician for at least six months (established-PCP) or not (no-PCP). Of the 173 enrolled patients, 91 (53%) patients had at least one visit with the PCMH-KD PCP. The rate of visits was higher in those in the no-PCP group compared with those in the established-PCP group (62% vs. 41%, respectively). Having more visits with the CHW was positively associated with having a visit with the PCMH-KD PCPs for both groups. Embedded CHWs within the care team played a role in facilithe uptake of PCMH-KD PCP. Lessons from this health system intervention can inform future approaches on the integration of PCPs and care coordination for CHD patients. Abstract : Patients on hemodialysis who had more visits with a community health worker were more likely to follow-up with a study-provided primary care physician.